2014
DOI: 10.1038/hr.2014.168
|View full text |Cite
|
Sign up to set email alerts
|

Gender influences the relationship between lung function and cardiac remodeling in hypertensive subjects

Abstract: Hypertensive patients are predisposed to left ventricular (LV) remodeling and frequently exhibit decline in lung function as compared with the general population. Here, we investigated the association between spirometric and echocardiographic data in non-smoking hypertensive subjects and the role of gender in this regard. In a cross-sectional study, 107 hypertensive patients (60 women) enrolled from a university outpatient clinic were evaluated by clinical, hemodynamic, laboratory and echocardiographic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In addition, studies have confirmed that lower BMI may be related to increased cardiovascular events and cardiac mortality 9 , 10 . Although it is well known that long-term COPD will be complicated more often with lung functional impairment and pulmonary heart disease, which is characteristically manifested as right-sided atrial and ventricular enlargement, several studies have reported that reduced left-sided cardiac filling (preload) was found in COPD patients 11 , 12 , and the association of impaired lung function with left-sided cardiac atrial and ventricular dimensional changes was more often seen in hypertensive women 13 . However, up to now, it is unclear whether BMI is related to the left-sided cardiac structural remodeling corresponding to different severity of lung functional reduction in COPD patients.…”
mentioning
confidence: 99%
“…In addition, studies have confirmed that lower BMI may be related to increased cardiovascular events and cardiac mortality 9 , 10 . Although it is well known that long-term COPD will be complicated more often with lung functional impairment and pulmonary heart disease, which is characteristically manifested as right-sided atrial and ventricular enlargement, several studies have reported that reduced left-sided cardiac filling (preload) was found in COPD patients 11 , 12 , and the association of impaired lung function with left-sided cardiac atrial and ventricular dimensional changes was more often seen in hypertensive women 13 . However, up to now, it is unclear whether BMI is related to the left-sided cardiac structural remodeling corresponding to different severity of lung functional reduction in COPD patients.…”
mentioning
confidence: 99%